Equity and Growth in a Globalizing World : Commission on Growth and Development - Kanbur, Ravi; Spence, Michael (World Bank, 2012)
The commission on growth and development was established in April 2006 in response to two insights: people do not talk about growth enough, and when they do, they speak with unearned conviction. The workshops turned out to be intense, lively affairs, lasting up to three days. It became clear that experts do not always agree, even on issues that are central to growth. But the Commission had no wish to disguise or gloss over these uncertainties and differences. And it did not want to present a false confidence in its conclusions beyond that justified by the evidence. While researchers will continue to improve people's understanding of the world, policy makers cannot wait for scholars to satisfy all of their doubts or resolve their differences. Decisions must be made with only partial knowledge of the world. One consequence is that most policy decisions, however well informed, take on the character of experiments, which yield useful information about the way the world works, even if they do not always turn out the way policy makers had hoped. It is good to recognize this fact, if only so that policy makers can be quick to spot failures and learn from mistakes. In principle, a commission on growth could have confined its attention to income per person, setting aside the question of how income is distributed. But this commission chose otherwise. It recognized that growth is not synonymous with development. To contribute significantly to social progress, growth must lift everyone's sights and improve the living standards of a broad swath of society. The Commission has no truck with the view that growth only enriches the few, leaving poverty undisturbed and social ills untouched.